Optimal Emission Pricing in the Presence of International Spillovers: Decomposing Leakage and Terms-of-Trade Motives - Christoph Böhringer; Andreas Lange; Thomas F. Rutherford (University of Oldenburg, Department of Economics, 2012)
Carbon leakage provides an efficiency argument for unilateral climate policy to differentiate emission prices in favor of emission-intensive and trade-exposed sectors. At the same time, differential emission pricing can be (mis-)used as a beggar-thy-neighbor policy to exploit terms of trade. Using an optimal tax framework, we propose a method to decompose the leakage motive and the terms-of-trade motive for emission price differentiation. We employ our method for a quantitative impact assessment of unilateral climate policy based on empirical data. We find that the leakage motive yields only small efficiency gains compared to uniform emission pricing. Likewise, the terms-of-trade motive has rather limited potential for strategic burden shifting. We conclude that the simple first-best rule of uniform emission pricing remains a practical guideline for unilateral climate policy design.
Keywords: H21; Q43; R13; D58; 330; optimal taxation; emission leakage; terms of trade; Umweltschutz; Internationale Umweltpolitik; Umweltbelastung; Treibhausgas-Emissionen; Luftverschmutzung; Emissionshandel; Preisdifferenzierung; Terms of Trade; USA; EU-Staaten